Finite element model updating of concrete arch dams affected by alkali-silica reaction using ambient vibration monitoring and dam surveillance data - Nyoni, Bukhosi (Department of Civil Engineering, 2025)
Dams are important structures whose safety in operation is critical owing to the socioeconomic impacts associated with their collapse. Alkali-Silica Reaction (ASR) is a deleterious chemical reaction that affects the performance and safety of numerous concrete dam structures around the world. To ensure dam safety, a well-structured dam surveillance program that includes ambient vibration monitoring is essential as it enables an in-depth understanding of the behaviour of a dam in operation. Additionally, structural behaviour analysis through numerical models such as finite element (FE) models, is a crucial aspect of dam safety evaluations that allows dam safety engineers to predict the current and future behaviour of dams under various load combinations. The challenge in finite element analysis (FEA) is generating an FE model that is representative of the observed behaviour and condition of the dam to be trusted and used for further study. This study sort to find the best updating parameters and finite element model updating approach to achieve representative and reliable finite element models for the safety assessment of arch dams affected by ASR. This was achieved through sensitivity analysis of the behaviour (both dynamic behaviour and static behaviour) of concrete arch dams to (i) geometrical properties, (ii) material properties and (iii) load effects on the dam-foundation-reservoir system, to identify the best updating parameters. Following which a model updating procedure was proposed and implemented. It was observed that the behaviour of concrete arch dams is subject to their geometric properties. Their dynamic behaviour was observed to be largely sensitive to the dam- foundation-reservoir system stiffness and water level whereas their thermal behaviour was sensitive to the system thermal properties. Additionally, it was observed that the dynamic response is not as sensitive to ASR loading as initially assumed. Based on these findings, the proposed finite element model updating procedure begins with the updating of the system stiffness using modal parameters, followed by the updating of the thermal properties, and then updating of the parameters critical to ASR modelling. The proposed multi-step model updating procedure was successfully implemented to update a finite element model for a case study double curvature arch dam affected by ASR achieving agreeable results between the measured and predicted behaviour observations.